علاقة الاتصال التنظيمي بفاعلية أداء العاملين بجامعة الوادي - فريوة، فاتح, معيزة، زكرياء (جامعة الوادي university of Eloued, 2021)
الملخص: هدفت هذه الدراسة الحالية الى التعرف على العلاقة بين " الاتصال التنظيمي بفاعلية أداء العاملين", وذلك انطلاقا من التساؤل الرئيسي الذي تمت صياغته كالاتي : هل هناك علاقة بين الاتصال التنظيمي وفاعلية أداء العاملين بجامعة الوادي ؟ تنطوي تحته تساؤلات فرعية جاءت على النحو التالي : - هل هناك علاقة بين الاتصال التنظيمي وانجاز المهام أداء العمال على مستوى جامعة الوادي؟ - هل هناك علاقة بين الاتصال التنظيمي تطوير أداء العاملين داخل جامعة الوادي ؟ - هل هناك علاقة بين الاتصال التنظيمي وجودة علاقات العمل في جامعة الوادي ؟ ولقد تم في هذه الدراسة الاعتماد على المنهج الوصفي التحليلي، فضلا عن استخدام الاستبيان في جمع المعلومات والبيانات من الميدان ,والذي تضمن (40) بندا توزعت على مجتمع البحث لقد تم تطبيق هذه الاداة على العينة العشوائية ,قوامه(100) مفردة وهم عمال من جامعة الوادي خلال سنة الجامعية 2020/2021 . ولقد أسفرت هذه الدراسة على النتائج التالية: - توجد علاقة ارتباطيه قوية وموجبة دالة احصائية بين الاتصال التنظيمي ودرجة فعالية أداء العاملين بجامعة الوادي - توجد علاقة ارتباطيه موجبة دالة احصائية درجة بين الاتصال التنظيمي ودرجة جودة الإنجاز في جامعة الوادي - توجد علاقة ارتباطيه موجبة دالة احصائية درجة بين الاتصال التنظيمي ودرجة تطوير أداء العاملين في جامعة الوادي. - توجد علاقة ارتباطيه موجبة دالة احصائية درجة بين الاتصال التنظيمي ودرجة جودة علاقات العمل في جامعة الوادي. Résumé : فرنسية أو انجلزية This current study aimed to identify the relationship between "organizational communication with the effectiveness of employee performance", based on the main question that was formulated as follows: Is there a relationship between organizational communication and the effectiveness of the performance of employees of the Valley University? It contains sub-questions as follows: - Is there a relationship between organizational communication and the completion of tasks the performance of workers at the level of the University of the Valley? - Is there a relationship between organizational communication and employee performance development within El Wadi University? - Is there a relationship between organizational communication and the quality of work relations at El-Wadi University? In this study, it was based on the descriptive analytical method, as well as the use of the questionnaire in collecting information and data from the field, which included (40) items distributed among the research community. Valley, during the university year 2020/2021. This study yielded the following results: - There is a strong and positive correlation with a statistical function between the degree of organizational communication and the degree of effectiveness of the performance of employees at El-Wadi University. - There is a positive, statistically significant, correlation between organizational communication and the degree of quality of achievement at El-Wadi University. - There is a positive, statistically significant, correlation between organizational communication and the degree of development of the performance of employees at El-Wadi University. - There is a positive, statistically significant, correlation between organizational communication and the degree of quality of work relations at El-Wadi University.
دراسة ميدانية لعينة من عمال جامعة الشهيد حمه لخضر بالوادي
مذكرة ماستر علم الاجتماع تخصص تنظيم وعمل
Keywords: الإتصال التنظيمي، أداء العاملين; Communication organisationnelle, performance des employés; Organizational communication, employee performance